Support for the Death Penalty Reinstatement as a Protest Attitude: The Role of Political Trust. (June 2023) - Peshkopia, Ridvan; Trahan, Adam
We argue that support for the reinstatement of capital punishment might reflect protest against an untrustworthy judicial system, framing this as a protest attitude. We test our argument with data from a probability sample of 2, 366 respondents in Albania collected in 2015 via a cell phone random digit dialing technique. We found that respondents' support for the reinstatement of the death penalty is associated with lack of trust in the country's judiciary but not necessarily respondents prioritizing the war on crime. Also, we found that skepticism toward European Union (EU) membership conditionality as a drive for the country's democratization is a good predictor of support for the reinstatement of the death penalty, but there is no evidence that respondents related their support for the country's EU membership with support for capital punishment.